Role of Robot Scientists and Artificial Intelligence in Drug discovery (International Journal of Engineering and Computer Science, 2017)
The paper gives an overview of the meaning of Artificial Intelligence, (AI) Advantages and disadvantages. There are several fields in AI-robotics, speech recognition and expert system-to name a few. Doing the laundry or the dishes may no longer seem a chore. Robots are programmed to perform these activities. The recent times saw the artificially developed robot “Eve” help in searching for new drugs.Eve uses a standardized form of assay to compute Boolean functions of compound properties. These assays can be quickly and cheaply engineered using synthetic biology, enabling more targets to be assayed for a given budget. Another discovery is the anti-cancer drugs which exhibited anti-malarial properties.